2021
DOI: 10.1111/cpr.13122
|View full text |Cite
|
Sign up to set email alerts
|

The role of Ca2+/Calcineurin/NFAT signalling pathway in osteoblastogenesis

Abstract: The bone remodelling process is closely related to bone health. Osteoblasts and osteoclasts participate in the bone remodelling process under the regulation of various factors inside and outside. Excessive activation of osteoclasts or lack of function of osteoblasts will cause occurrence and development of multiple bone‐related diseases. Ca2+/Calcineurin/NFAT signalling pathway regulates the growth and development of many types of cells, such as cardiomyocyte differentiation, angiogenesis, chondrogenesis, myog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 126 publications
(234 reference statements)
0
14
0
Order By: Relevance
“…CaM also dephosphorylates NFAT, which in turn enters the nucleus and upgrades the transcription of osteogenic-related genes. 149 Overall, when cells adhere to a rough topography surface, they have a more extended cellular morphology and a responsive intracellular tension that mediates cytoskeletal remodeling. The contractile forces on the cytoskeleton alter the expression of intracellular genes by changing the nuclear morphology and activating YAP/TAZ and calcium channels.…”
Section: Downstream Signaling Pathways That Regulate Gene Expressionsmentioning
confidence: 99%
See 1 more Smart Citation
“…CaM also dephosphorylates NFAT, which in turn enters the nucleus and upgrades the transcription of osteogenic-related genes. 149 Overall, when cells adhere to a rough topography surface, they have a more extended cellular morphology and a responsive intracellular tension that mediates cytoskeletal remodeling. The contractile forces on the cytoskeleton alter the expression of intracellular genes by changing the nuclear morphology and activating YAP/TAZ and calcium channels.…”
Section: Downstream Signaling Pathways That Regulate Gene Expressionsmentioning
confidence: 99%
“…CaM also dephosphorylates NFAT, which in turn enters the nucleus and upgrades the transcription of osteogenic-related genes. 149…”
Section: How Stem Cells Recognize the Cues Of Topographymentioning
confidence: 99%
“…It has been shown that normal body metabolism can produce reactive oxygen species (ROS), either endogenously by nicotinamide adenine dinucleotide phosphate oxidase (NOX) or as a by-product of the mitochondrial electron transport chain ( Ren et al, 2021 ; Zhu et al, 2022 ). ROS contains superoxide anion radicals (O 2 −), hydrogen peroxide (H 2 O 2 ), hydroxyl radicals (-OH) and nitric oxide (NO) ( Madreiter-Sokolowski et al, 2020 ).…”
Section: Receptor Activator Of Nuclear Factor-κb Ligand-mediated Clas...mentioning
confidence: 99%
“…Bones respond to mechanical stimuli and activate corresponding signaling pathways including calcium ions, integrins, prostaglandins (PG), and nitric oxide (NO) ( Huang and Ogawa, 2010 ) ( Figure 1C ). The level of inositol 1,4,5-triphosphate (IP3) promotes the release of calcium ions and increases its cytoplasmic concentration, then activates Wnt pathway and triggers BMP-2 ( Ren et al, 2021 ). Focal adhesion kinase (FAK) is an intracellular component of the integrin signaling pathway, which eliminates osteogenic response when inactivated.…”
Section: Molecular Mechanisms Regulating Asc Osteogenesismentioning
confidence: 99%